An Analysis of Deixis in Song ‘Popular’ & ‘Yes, And’ for Teaching and Learning Practice for ELT Student - Maimunah Maimunah Mudjahid (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
The objective of this study is to examine the utilization of deixis in song lyrics. Employing a qualitative descriptive approach, the research focuses on the lyrics of two songs, “Popular” and “Yes, and,” performed by Ariana Grande. The analysis of these songs revealed the presence of various deixis types, with distinct frequencies observed in each song. Specifically, the identified deixis categories include personal deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis. The findings for “Popular” show 55 of personal deixis, 2 instances of spatial deixis, 7 of temporal deixis, 2 of discourse deixis, and 1 social deixis. In contrast, the analysis of “Yes, And” revealed 63 instances of personal deixis, 17 instances of spatial deixis, 1 temporal deixis, 2 of discourse deixis, and 3 of social deixis. Based on these results, it can be concluded that personal deixis is the most frequently used type in both songs. The result of this research shown how deixis analysis in song lyrics contribute in teaching and learning for ELT students.